The Role of Shaykh Al-Linggi in the Preservation of the Doctrine of Ahl al-Sunnah wa al-Jama'ah in the Malay World - Wan Zailan Kamaruddin bin Wan Ali (UIN Sunan Gunung Djati Bandung, 2022)
The Malay world in the Southeast Asian region holds various Islamic -based scholarly and intellectual treasures, which have yet to be fully explored. Efforts to uncover valuable old treasures must be made continuously because of its various interests, especially in the framework of the development and advancement of the ummah. The region also saw the birth of influential Malay Muslim thinkers who drove the ummah towards excellence and glory. One of the figures discussed in this paper with the mission of